Socio-Economic Impact of the Mobile Phone based Agricultural Extension - Mittal, Surabhi; Mehar, Mamta (New India Publishing Agency, 2014)
The content of the book comprises of country chapters on mobile phone applications for agricultural extension from Asia, Africa, Latin America and Europe along with chapters on global review on m-agriculture initiatives, content generation process and socio-economic impact of mobile phone based agro-advisory services. This book delves into the development of mobile phone based agro-advisory and their content, delivery mode, business model and utility and provides an insight into the evolution of mobile phones as an extension tool in different countries across the globe. The book will provide valuable insights on m-agriculture initiatives for agricultural extension around the world to agricultural students, extension professionals, researchers and policy makers both for understanding them and working on them. The lessons from the m-agriculture initiatives can guide the mode of implementation and evolution of mobile based advisory services in agriculture.